Benzidine/Quinoidal‐Benzidine‐Linked, Superbenzene‐Based π‐Conjugated Chiral Macrocycles and Cyclophanes. Issue 24 (7th April 2020) - Li, Guangwu; Matsuno, Taisuke; Han, Yi; Phan, Hoa; Wu, Shaofei; Jiang, Qing; Zou, Ya; Isobe, Hiroyuki; Wu, Jishan
Abstract: Synthesis of fully conjugated cyclophanes containing large‐size polycyclic aromatics is challenging. Now, three benzidine‐linked, hexa‐peri‐hexabenzocoronene (superbenzene)‐based ortho‐, para‐, and meta‐cyclophanes are synthesized through intermolecular Yamamoto coupling reaction of structurally pre‐organized precursors. Subsequent oxidative dehydrogenation gave the corresponding quinoidal benzidine‐linked cyclophanes. Their geometries were confirmed by X‐ray crystallographic analysis and their electronic properties were investigated by electronic absorption, cyclic voltammetry, and DFT calculations. The quinoidal benzidine‐linked cyclophanes show thermally populated paramagnetic activity with a relatively large singlet‐triplet energy gap. Two enantiomers for the ortho‐cyclophanes (1‐NH and 1‐N ) were isolated and their chiral figure‐of‐eight macrocyclic structures were identified. The cage‐like cyclophanes 2‐NH and 3‐NH with concave surface can selectively encapsulate fullerene C70 . Abstract : Big, handed, super ! An efficient synthesis of benzidine/quinoidal benzidine‐linked, superbenzene‐based fully conjugated macrocycles and cage‐like cyclophanes has been developed. These show chiral optical properties, paramagnetic activity, and topology‐dependent electronic properties, dynamic behavior, and host–guest chemistry.